REseau MOllusques des Rendements Aquacoles huitre creuse (REMORA) - Fleury, Pierre-gildas; Simonne, Charlotte; Claude, Serge; Palvadeau, Hubert; Guilpain, Patrice; D'Amico, Florence; Le Gall, Patrik; Vercelli, Catherine; Pien, C (2005)
The network REMORA by IFREMER quarterly follows each year 2 batches of Pacific cupped oysters Crassostrea gigas ("juveniles"= 1 year old; and "adults" = 2 years old) on various sites among the main French oyster areas. The network monitored 46 sites in 2004, including the 7 new sites added in 2003. The network REMORA thus assess seasonal survival, growth and quality of cupped oysters. It is a tool for trend estimations, ecosystem management and a reference frame for scientific studies. Globally speaking, the year 2004 was a good year for oyster farming, with a low mortality and a fast growth. The rearing yield (survival x growth) reached 2.0 for adults instead of 1.8 usually. However, the meat index remained close to the average inter annual data. Mortalities remained low (9% and 12% in average respectively for adults and juveniles) with rare exceptions in some more sensible sites : Morlaix, Pen-Bé, Marennes and Tès (Arcachon, only juveniles for this site). The growth gain reached high values: +36 g for adults and +28 g for the juveniles. However the differences between the sites were very important with the return of a good growth in the Thau lagoon (> 130 g in Bouzigues), and lower results in areas from Pays de Loire to Arcachon. The average meat index was 9.7 in December. All the batches reached the professional label "Fines" (meat index > 6.5), and several of them the label "Spéciales" (>10.5). After a light increase of the Polydora index (IP) in 2003, the year 2004 confirmed the decline of this infestation (IP = 0.22), as observed since 2000, especially in the Pays de Loire, Marennes-Oléron and overall in the Thau lagoon where most oysters are free of the parasite. Le réseau IFREMER /REMORA suit trimestriellement chaque année 2 lots d'huîtres Crassostrea gigas ("juvéniles" = 1 an et "adultes" = 2 ans) répartis entre différentes stations dans les principaux secteurs ostréicoles français. Les 7 points de suivis ajoutés au réseau en 2003 ont été maintenus. Le réseau REMORA permet ainsi d'évaluer ...